2011
DOI: 10.1084/jem.20110398
|View full text |Cite
|
Sign up to set email alerts
|

TAK1 in brain endothelial cells mediates fever and lethargy

Abstract: Expression of the MAP kinase kinase kinase TAK1 in brain endothelial cells is needed for production of prostaglandin E2, and for induction of fever and sickness behavior, in response to peripheral inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
146
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 109 publications
(157 citation statements)
references
References 30 publications
9
146
2
Order By: Relevance
“…Blood-borne IL-1β signaling to CNS is completely dependent on endothelial IL-1R1 (Ching et al, 2007), which at BBB was also shown to be highly expressed on endothelial cells and not on perivascular cells (Konsman et al, 2004). A later study in which the brain endothelial IL-1β signaling was specifically targeted by TAK1 deletion in brain endothelial cells resulted in blunted fever response and decreased locomotion (lethargy) (Ridder et al, 2011). However, intraperitoneally injected IL-1β may signal to CNS through other pathways, probably by activating peripheral macrophages (Ching et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Blood-borne IL-1β signaling to CNS is completely dependent on endothelial IL-1R1 (Ching et al, 2007), which at BBB was also shown to be highly expressed on endothelial cells and not on perivascular cells (Konsman et al, 2004). A later study in which the brain endothelial IL-1β signaling was specifically targeted by TAK1 deletion in brain endothelial cells resulted in blunted fever response and decreased locomotion (lethargy) (Ridder et al, 2011). However, intraperitoneally injected IL-1β may signal to CNS through other pathways, probably by activating peripheral macrophages (Ching et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…These studies include work on TLR4 chimeric mice (Chakravarty and Herkenham, 2005;Steiner et al, 2006b), endothelial specific IL-1R1 KO mice (Ching et al, 2007), brain endothelial TAK1 KO mice, i.e. specific brain endothelial IL-1 signaling blockage (Ridder et al, 2011), and MyD88 chimeric mice (Gosselin and Rivest, 2008) (Figure 9). …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations